An evaluation of the relevance of the UP School of Library and Information Studies' (SLIS) Master of Library and Information Science (MLIS) program through its graduates' perception - Racines, Christian Q.; Santos, Yhna Therese P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
The Master of Library and Information Science (MLIS) program had been offered by the UP School of Library and Information Studies (SLIS) since 1962. Since then, it has produced a number of graduates that has excelled in the field of library and information science.
This study evaluated the relevance of the MLIS program of the UP SLIS through the perception of its own graduates. The study found out that the graduates think the program is very good and it is relevant to them especially on their current jobs and careers. The graduates even noted that having the master's degree from the program helped them understand more about information education and library science is not just about books but it is also about organization, management, interpretation and preservation of information.
Overall, the graduates perceived the MLIS program to be relevant. However, several suggestions are given by the graduates for the improvement of the MLIS program of the UP SLIS. It is recommended that the program should organize publicity events and information campaigns to encourage more students to apply to the program. Also, they suggested that the school should increase the number of practicing librarians as instructors for the course. Another suggestion is that the program should have more hands-on exercises in its classes. Lastly, the graduates recommend that the school upgrade its facilities and equipment to further enhance the interest and learning of its students.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library Science -- Curricula; Library education (Continuing education) -- Philippines